SiMPLOD, a Structure‐Integrated Database of Collagen Lysyl Hydroxylase (LH/PLOD) Enzyme Variants. (12th March 2019) - Scietti, Luigi; Campioni, Matteo; Forneris, Federico
ABSTRACT: PLOD genes encode for procollagen lysyl hydroxylase enzymes (LH/PLOD), a family of proteins essential for collagen biosynthesis. Several mutations affect these genes, causing severe disorders, such as Ehlers‐Danlos and Bruck syndrome, as well a connective tissue disease with phenotype resembling osteogenesis imperfecta caused by lack of LH3 functions. The recently determined three‐dimensional (3D) structures of the full‐length human LH3/PLOD3 isoform, together with the structure of a fragment of a viral LH/PLOD homolog, are now allowing molecular mapping of the numerous disease‐causing mutations, providing insights often suitable for the interpretation of the resulting disease phenotypes. However, the added value of molecular structure interpretation is affected by the limited accessibility of complex molecular data to scientific communities lacking direct expertise in structural biology. In this work, we present a Structurally‐integrated database for Mutations of PLOD genes (SiMPLOD), a publicly‐available manually‐curated online database with an embedded molecular viewer interface for the visualization and interpretation of LH/PLOD mutations on available molecular models. Each SiMPLOD entry is accompanied by manual annotations extrapolated from literature references and comments about the localization of the amino acid variants on the molecular structure. Additional links to the appropriate online resources for clinically‐relevant as well as biochemical data are also provided in a standardized format. The web application is available at http://fornerislab.unipv.it/SiMPLOD . © 2019 American Society for Bone and Mineral Research.